2005
DOI: 10.1063/1.2058193
|View full text |Cite
|
Sign up to set email alerts
|

Optical and morphological investigation of backward-deposited layer induced by laser ablation of steel in ambient air

Abstract: The irradiation of a steel surface in atmospheric pressure ambient was performed to study the surface nanostructuring resulting from the formation of a backward-deposited layer. The dynamics of the plume expansion and of the nanoparticle deposition process were investigated by in situ time-resolved optical analysis. Scanning electron microscopy and atomic force microscopy were employed to investigate the morphological characteristics of the backward deposited layer. The observations revealed a particular shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…The complicated hydrodynamics of the ablation plume with formation of shock waves and vortical structures brings ablated particles back to the irradiated surface [19,31,89,90]. During mixing with air, ablated particles can experience oxidation and form clusters.…”
Section: Backward Deposition Of Ablation Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complicated hydrodynamics of the ablation plume with formation of shock waves and vortical structures brings ablated particles back to the irradiated surface [19,31,89,90]. During mixing with air, ablated particles can experience oxidation and form clusters.…”
Section: Backward Deposition Of Ablation Productsmentioning
confidence: 99%
“…As a result, the redeposited material represents a nanostructured oxide layer. In [89], detailed studies of surface nanostructuring was reported for steel samples irradiated by a XeCl excimer laser (308 nm, pulse duration of 25 ns) in air under atmospheric pressure. Due to the high pressure of the surrounding gas, the laser-produced plasma remains confined close to the sample surface, so that the ablated and formed within the plume species are deposited around the spot area by backward flux (Figure 11a).…”
Section: Backward Deposition Of Ablation Productsmentioning
confidence: 99%
“…3͑a͒ ͑ii͔͒ is also observed in case of helium ambient; however, magnetic field gradient is not as strong as in the case of argon ambient because of the comparatively lower value of ␤ due to efficient cooling in helium ambient and hence leading to lower backscattering. 19 The net result being significantly low structured or unstructured deposition in combined ambient of helium and magnetic field as compared to argon and magnetic field. Figures 4͑a͒ and 4͑b͒ show XRD pattern of Cu nanoclusters deposited back on the copper target.…”
Section: Resultsmentioning
confidence: 99%
“…The plume expansion being slow in presence of argon makes it stay for longer time compared to that of helium ambient near the target surface. IPLD essentially relies on the backscattering during the expansion of the plume and its lateral expansion, 18,19 it in turn is dependent on the atomic mass of the ambient gas. 20 Thus the combined effect of the confined plasma near to the target 9 and enhanced backscattering may lead to enhanced deposition rate in presence of argon compared to that of helium.…”
Section: Resultsmentioning
confidence: 99%
“…According to Golberg et al [36] the BN plume interaction with nitrogen gas strongly contributes to the nanostructures formation. Pereira et al [37] have recently discussed a backscattering of the ablated products in form of clusters, which may also be considered as elementary building units for the observed nanorods. The spatial distribution of these clusters is generally not uniform and mostly concentrated at the perimeter of the ablated area, which is explained by vortices formation favoring transversal mass transport.…”
Section: Discussionmentioning
confidence: 99%